KONTEN DAKWAH TIKTOK DAN IMPLIKASINYA TERHADAP PENDIDIKAN ISLAM TENTANG ADAB BIRRUL WALIDAIN PADA REMAJA MASJID NURUL HAQ TOMBA - Adiela Fayyaza; La Jusu; Jufri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the perceptions of youth members of Masjid Nurul Haq Tomba toward Islamic preaching content on TikTok and to analyze its implications for the formation of birrul walidain conduct within the framework of Islamic education. The phenomenon underlying this research is the measurable success of TikTok-based digital dakwah in cultivating awareness and filial behavior among mosque youth, a reality that surpasses the theoretical expectation which asserts that the formation of Islamic conduct cannot rely solely on digital media. This study employed a qualitative approach using a case study design conducted directly at Masjid Nurul Haq Tomba. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the interactive analysis model of Miles et al., and validated through source triangulation and technique triangulation. The findings reveal that youth perceptions were positively shaped through three interconnected aspects, namely message comprehension, content appeal, and critical trust toward the preacher, all of which were reinforced by the religious mentorship environment of the mosque. The implications of TikTok dakwah content on birrul walidain conduct unfolded in successive layers, from the growth of value awareness and concrete attitudinal change to the internalization of filial behavior in daily life. The central finding of this study affirms that digital dakwah and mosque-based Islamic education are not competing forces but mutually reinforcing ones. This research contributes to the achievement of SDGs Goal 4 on quality education and Goal 16 on peace and strong institutions through the formation of a morally grounded and family-harmonious younger generation.